Cold-Inducible RNA-Binding Protein Regulates Cardiac Repolarization by Targeting Transient Outward Potassium Channels. Issue 10 (8th May 2015) - Li, Jun; Xie, Duanyang; Huang, Jian; Lv, Fei; Shi, Dan; Liu, Yi; Lin, Li; Geng, Li; Wu, Yufei; Liang, Dandan; Chen, Yi-Han
<x xml:space="preserve">Abstract</x> Rationale: Cold-inducible RNA-binding protein (CIRP) is constitutively expressed at low levels across various tissues. It is rapidly upregulated by multiple stresses, underlying a general role for CIRP in organic adaptations to pathophysiological conditions. However, the role of CIRP in the heart remains unclear. Objective: To examine the biofunctions of CIRP in the mammalian heart. Methods and Results: Rats with targeted disruption of Cirp were generated using the TALEN (transcription activator-like effector nucleases)-based genome editing technique. The Cirp-knockout rats had structurally and functionally normal hearts. Resting ECG recordings revealed a short rate-corrected QT (QTc) interval in Cirp-null rats without any abnormalities in PR interval, RR interval or QRS waves as compared to wild-type animals. The shortened QTc interval from Cirp ablation was tightly linked to an abbreviated action potential duration in cardiac myocytes, which was attributable to increased transient outward potassium current (Ito). Furthermore, our findings uncovered that CIRP protein selectively bonded to KCND2 and KCND3 mRNAs encoding the functional α-subunits of Ito channel proteins. CIRP deficiency did not change the transcriptional activity of KCND2 or KCND3, but it facilitated their translation. Cirp knockout had no effect on the functional expression of ion channels other than Ito channels. Conclusions: CIRP modulates cardiac repolarization by negatively adjusting the expression and function of Ito channels. Our study may open a window to decipher the potential function of RNA-binding proteins in bioelectric activity.